Uncovering EEG correlates of covert attention in soccer goalkeepers: Towards innovative sport training procedures - Jeunet, C.; Tonin, L.; Albert, L.; Chavarriaga, R.; Bideau, B.; Argelaguet, F.; del R. Millan, J.; Leécuyer, A.; Kulpa, R. (Scientific Reports, 2020)
Advances in sports sciences and neurosciences offer new opportunities to design efficient and motivating sport training tools. For instance, using NeuroFeedback (NF), athletes can learn to self-regulate specific brain rhythms and consequently improve their performances. Here, we focused on soccer goalkeepers` Covert Visual Spatial Attention (CVSA) abilities, which are essential for these athletes to reach high performances. We looked for Electroencephalography (EEG) markers of CVSA usable for virtual reality-based NF training procedures, i.e., markers that comply with the following criteria: (1) specific to CVSA, (2) detectable in real-time and (3) related to goalkeepers` performance/expertise. Our results revealed that the best-known EEG marker of CVSA—increased a-power ipsilateral to the attended hemi-field— was not usable since it did not comply with criteria 2 and 3. Nonetheless, we highlighted a significant positive correlation between athletes` improvement in CVSA abilities and the increase of their a-power at rest. While the specificity of this marker remains to be demonstrated, it complied with both criteria 2 and 3. This result suggests that it may be possible to design innovative ecological training procedures for goalkeepers, for instance using a combination of NF and cognitive tasks performed in virtual reality.